“La guerra que no hemos visto” and the activation of speech - Rubiano, Elkin (Estudios de Filosofía, 2018)
This paper offers an analysis of the artwork “La guerra que no hemos visto. Un proyecto de memoria histórica” (the war we have not seen. A project on historical memory”) by the artist Juan Manuel Echavarría. The paper shows how the meaning of the artwork is constructed in the context of two different experiences with transitional justice in Colombia: La ley de Justicia y Paz (2005) (peace and justice law) and Acuerdo final para la terminación del conflicto y la construcción de una paz estable y duradera (2016) (Final settlement for the termination of conflict and building of a lasting and stable peace). “La guerra que no hemos visto” functions as a dispositive to activate conversations in which the necessary conditions to hear the voices of anonymous combatants that are silenced (their lives are threatened) are built. Simultaneously this project is contrasted with other similar initiatives on which, instead of prompting dialogue, a simulacrum is built.